Against supererogationism - Van Niekerk, Jason Bradley (Rhodes University, Faculty of Humanities, Department of Philosophy, 2006)
In this thesis, I argue that we have no reason to accept the existence of a category of supererogatory moral goods: that is, good acts that carry no pressure to bring them about. Despite the counterintuitive nature and suspicious provenance of the concept, Supererogationism is the orthodoxy in Ethics, and I examine promising but unsuccessful responses to it by Peter Singer and Kwame Gyekye. Responding in particular to David Heyd's Supererogationism - but also to J. O. Urmson, Susan Wolf, and Jonathan Dancy - I develop an account of the principle "Good implies Ought" that does not entail absurd over-obligation. I argue that this Anti-Supererogationist model stands up to the four strongest arguments against such a position, and that it embraces a more accurate account of the relation between values and oughts than Supererogationists are capable of supplying. Finally, I sketch a detailed eudaimonist account of the principle umuntu ngumuntu ngabantu - that our commitment to the good of others stems from our flourishing being caught up with theirs.
Keywords: Supererogation; Supererogation -- History; Values; Ethics -- History